2001
DOI: 10.1097/00001756-200108080-00037
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of rCBF in Alzheimer's disease patients with delusions of theft

Abstract: We investigated the neural substrate of the delusion of theft in patients with Alzheimer's disease (AD). Nine AD patients with only one type of delusion (delusions of theft) and nine age, cognitive function-matched AD patients without any type of delusions were selected from 334 consecutive outpatients of Ehime University Hospital. All subjects underwent (99m)Tc-HMPAO SPECT scanning, and SPECT images were analyzed by Statistical Parametric Mapping (SPM). AD patients with delusions of theft showed significant h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 18 publications
2
30
0
Order By: Relevance
“…However, it has been suggested that different types of delusions in AD patients have discrete neurological pathophysiologies. In line with this hypothesis, a previous study demonstrated that rCBF in the medial posterior parietal region was decreased in patients with delusions of theft compared with those without delusions [17] . In accordance with this result, we also found significant hypoperfusion in the posterior regions in patients with delusions of theft.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, it has been suggested that different types of delusions in AD patients have discrete neurological pathophysiologies. In line with this hypothesis, a previous study demonstrated that rCBF in the medial posterior parietal region was decreased in patients with delusions of theft compared with those without delusions [17] . In accordance with this result, we also found significant hypoperfusion in the posterior regions in patients with delusions of theft.…”
Section: Discussionmentioning
confidence: 54%
“…When the liberal threshold (p ! 0.01, uncorrected, k 1 50), which is similar to the threshold used in the previous studies [11,12,17] , was applied, the rCBF in the posterior cingulate and the bilateral cerebellum was significantly decreased in those with delusions ( table 4 ; fig. 2 ).…”
Section: Two-sample T Testmentioning
confidence: 81%
“…Several researchers have also demonstrated relationships between delusions and cerebral regions in AD. For example, Fukuhara et al [30] found an association between delusions and right medial posterior parietal hypoperfusion. Staff et al [9] noted a relation between delusions and right frontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…77.3% of Japanese females over 50 years of age manage their family living expenses alone (Ehime Women's Foundation, 2000). Biological aspects such as cortical dysfunction (Ponton et al, 1995;Staff et al, 1999;Fukuhara et al, 2001) as well as psychosocial and environmental aspects such as the contribution rate to household matter and living with or without caregivers as well as biological aspects such as cortical dysfunction (Ponton et al, 1995;Staff et al, 1999;Fukuhara et al, 2001) may be important to consider when to exploring AD delusions in future studies.…”
Section: Discussionmentioning
confidence: 99%